2023
DOI: 10.3389/fphar.2023.1163970
|View full text |Cite
|
Sign up to set email alerts
|

ANO1-downregulation induced by schisandrathera D: a novel therapeutic target for the treatment of prostate and oral cancers

Abstract: Anoctamin 1 (ANO1), a drug target for various cancers, including prostate and oral cancers, is an intracellular calcium-activated chloride ion channel that plays various physiopathological roles, especially in the induction of cancer growth and metastasis. In this study, we tested a novel compound isolated from Schisandra sphenanthera, known as schisandrathera D, for its inhibitory effect on ANO1. Schisandrathera D dose-dependently suppressed the ANO1 activation-mediated decrease in fluorescence of yellow fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Previous studies have reported that a decrease in ANO1 protein levels can lead to decreased cancer cell viability ( Seo et al, 2017 ; 2021 ; Park et al, 2023 ). To establish whether vitekwangin B decreased ANO1 protein levels, PC3 ANO1-KO cells were generated using the CRISPR-Cas9 system, and ANO1 protein levels in PC9 and CHO cells were verified ( Figures 2A, B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that a decrease in ANO1 protein levels can lead to decreased cancer cell viability ( Seo et al, 2017 ; 2021 ; Park et al, 2023 ). To establish whether vitekwangin B decreased ANO1 protein levels, PC3 ANO1-KO cells were generated using the CRISPR-Cas9 system, and ANO1 protein levels in PC9 and CHO cells were verified ( Figures 2A, B ).…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological inhibition of ANO1 inhibits the growth of various types of cancer cells ( Seo et al, 2017 ; Seo et al, 2021 ; Park et al, 2023 ). Vitekwangin B was tested to determine whether it inhibited the growth of prostate cancer and NSCLC cells by decreasing ANO1 protein levels ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation